Deterrence-From Cold War to Long War Lessons from Six Decades of RAND Research - Long, Austin (RAND Corporation, 2008)
Since its inception six decades ago, the RAND Corporation has been one of the key institutional homes for the study of deterrence. This book examines much of this research for lessons relevant to the current and future strategic environment. It is therefore part intellectual history and part policy recommendation, intended to encourage debate and discussion on how deterrence can best be incorporated into U.S. strategy.